Research for the future: Investments for efficiency, sustainability, and equity - Stads, Gert-Jan; Wiebe, Keith D.; Nin-Pratt, Alejandro; Sulser, Timothy B.; Benfica, Rui; Reda, Fasil; Khetarpal, Ravi (International Food Policy Research Institute, 2022)
Food systems everywhere are facing major new challenges. Shocks caused by COVID-19 have currently seized our attention, but the pandemic has also accentuated persistent problems of poverty, hunger and malnutrition, population growth, and pressure on natural resources, notably land, water, and biodiversity. Adding to these challenges, climate change poses a serious threat to food security and livelihoods as greenhouse gas (GHG) emissions continue to rise. Changing temperatures, highly variable precipitation, shifting growing seasons, and extreme weather events are already making agricultural yields and prices more volatile, with rural areas across the world feeling the effects most profoundly. Yet, as the world’s population moves toward 9 or 10 billion by 2050, unprecedented increases in global food production — of at least 60 percent over 2005–2007 levels — will be needed to meet growing demand.